Students' Perception of Kahoot Media Utilization in Arabic Language Learning - Agil, Sahirin; Intes, Amina; Guilin, Xie (Journal International of Lingua and Technology, 2022)
Learning media is one of the most important parts that affects the success of the student learning process. The selection and utilization of appropriate and interesting media will have a positive impact on the success of student learning. However, the utilization of learning media, especially those based on information and communication technology for learning Arabic, is still not widely found and is rarely done. The purpose of this study was conducted to determine the effect of using kahoot media at State Senior High School 4 Jakarta. The method used in this research is quantitative method with survey technique using questionnaire instrument, 10th grade students of State Senior High School 4 Jakarta totaling 50 people as subjects in this study. This research technique aims to determine whether kahoot media has an effect on Arabic language skills by using kahoot media through cellphones. This learning is done using a cellphone because material from printed books has been used as a source by educators. Teachers are expected to be able to utilizing learning media as a means of supporting teaching and learning activities to create interactive learning for students so as to improve students' ability to understand lessons delivered by an educator which will affect learning outcomes. Based on the results of this study, it can be seen that the use of learning media games for students can be applied in the learning process and for further researchers can use this learning media in Arabic subjects.